2024
DOI: 10.1002/hem3.45
|View full text |Cite
|
Sign up to set email alerts
|

Integrative single‐cell expression and functional studies unravels a sensitization to cytarabine‐based chemotherapy through HIF pathway inhibition in AML leukemia stem cells

Talia Velasco‐Hernandez,
Juan L. Trincado,
Meritxell Vinyoles
et al.

Abstract: Relapse remains a major challenge in the clinical management of acute myeloid leukemia (AML) and is driven by rare therapy‐resistant leukemia stem cells (LSCs) that reside in specific bone marrow niches. Hypoxia signaling maintains cells in a quiescent and metabolically relaxed state, desensitizing them to chemotherapy. This suggests the hypothesis that hypoxia contributes to the chemoresistance of AML‐LSCs and may represent a therapeutic target to sensitize AML‐LSCs to chemotherapy. Here, we identify HIFhigh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Their data support the potential of targeting hypoxia-induced gene regulation in leukemic stem cells (LSC) in AML. 2 Oxygen homeostasis is transcriptionally regulated by a family of hypoxia-inducible factors (HIF) that act as transcriptional activators and repressors. Heterodimeric HIFs are formed by a constitutively expressed HIF1β subunit (encoded by ARNT) and a HIF1/2/3α (encoded by HIF1A, EPAS1, HIF3A, respectively).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Their data support the potential of targeting hypoxia-induced gene regulation in leukemic stem cells (LSC) in AML. 2 Oxygen homeostasis is transcriptionally regulated by a family of hypoxia-inducible factors (HIF) that act as transcriptional activators and repressors. Heterodimeric HIFs are formed by a constitutively expressed HIF1β subunit (encoded by ARNT) and a HIF1/2/3α (encoded by HIF1A, EPAS1, HIF3A, respectively).…”
mentioning
confidence: 99%
“…Collectively, Velasco et al unraveled the LSC transcriptomes and particularly hypoxia-regulated genes at the single-cell level from AML patients at diagnosis and relapse and provided experimental evidence of synergistic antileukemic activity of small molecule HIF inhibitors and Ara-C in vitro and in vivo. 2 With the development of easy-to-perform experimental platforms, the number of studies that report AML transcriptomes at the single-cell level is rapidly increasing. 4 In their work, Velasco et al revealed the gene expression signatures of over 100,000 primary blasts from AML patients of the most prevalent genetic subgroups.…”
mentioning
confidence: 99%